2019
DOI: 10.1080/1744666x.2019.1699058
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs in the management of cardiovascular risk in inflammatory joint diseases

Abstract: Introduction: Increased cardiovascular (CV) morbidity and mortality is observed in inflammatory joint diseases (IJDs) such as rheumatoid arthritis, ankylosing spondylitis and psoriatic arthritis. However, the management of CV disease in these conditions is far from being well established. Areas covered: This review summarizes the main epidemiologic, pathophysiological and clinical risk factors of CV disease associated with IJDs. Less common aspects on early diagnosis and risk stratification of the CV disease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 127 publications
0
16
0
Order By: Relevance
“…In addition, there are other aspects contributing to cardiovascular risk in patients with chronic inflammatory rheumatic diseases, including organic diseases, psychological illnesses, socioeconomic factors, and miscellany conditions such as low vitamin D levels and hyperhomocysteinem. 81 Future study is needed to explore the association of more factors with the risk of MACEs in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are other aspects contributing to cardiovascular risk in patients with chronic inflammatory rheumatic diseases, including organic diseases, psychological illnesses, socioeconomic factors, and miscellany conditions such as low vitamin D levels and hyperhomocysteinem. 81 Future study is needed to explore the association of more factors with the risk of MACEs in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…The QRISK2 is the most widely used scale in the UK while the Framingham and American College of Cardiology/ American Heart Association (ACC/AHA) scale is more widely used in the US and Canada. In contrast to the SCORE scale, they establish the 10-year risk of major and non-major coronary events and classify patients into low (<10%), intermediate (10-20%), and high (20%) risk 3 . There is evidence that these algorithms (Framingham, ACC/AHA, and SCORE) underestimate because they do not include specific risk factors or overestimate (QRISK2) the true cardiovascular risk in patients with RA [2][3][4] .…”
Section: Identification Of Subclinical Atherosclerosis and Risk Stratificationmentioning
confidence: 99%
“…In contrast to the SCORE scale, they establish the 10-year risk of major and non-major coronary events and classify patients into low (<10%), intermediate (10-20%), and high (20%) risk 3 . There is evidence that these algorithms (Framingham, ACC/AHA, and SCORE) underestimate because they do not include specific risk factors or overestimate (QRISK2) the true cardiovascular risk in patients with RA [2][3][4] . For this reason, new tools have been developed to assess individual cardiovascular risk in patients with RA, such as the Extended Risk Score RA (ERS-RA).…”
Section: Identification Of Subclinical Atherosclerosis and Risk Stratificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, even if the findings of the Vergneault study 14 are confirmed in future larger and preferably longitudinal studies, the routine application of the DAS28-GGT is unlikely to significantly reduce the need for systematic formal CVD risk evaluation in RA. Moreover, besides the currently recommended need for consistent comprehensive traditional CVD risk factor recording in patients with RA, there is increasing evidence in support of a need for the complementary performance of noninvasive imaging, particularly carotid artery ultrasound, to optimize CV risk evaluation in many patients with RA 1,2,3,23 . This may be most important in RA patients from low or middle income populations such as black Africans in whom the Framingham score and SCORE are not useful in identifying high-risk atherosclerosis 2,24 .…”
mentioning
confidence: 99%